Conservation actions benefit the most threatened species: A 13‐year assessment of Alliance for Zero Extinction species. Issue 10 (28th July 2021) - Luther, David; Cooper, William Justin; Wong, Jesse; Walker, Margaretta; Farinelli, Sarah; Visseren‐Hamakers, Ingrid; Burfield, Ian J.; Simkins, Ashley; Bunting, Gill; Brooks, Thomas M.; Dicks, Kara; Scott, Janet; et al.
Abstract: More species in the world are threatened with extinction today than at any other time in recent history. In 2005, the Alliance for Zero Extinction (AZE; https://zeroextinction.org/ ) released its first inventory of highly threatened species (i.e., those listed as Critically Endangered or Endangered on the IUCN Red List) that are effectively confined to a single site. Updates were released in 2010 and 2018. Here we identify the species removed from the list in these updates, determine the reasons for these removals, identify species that no longer qualify as AZE species as a result of conservation actions, and examine which conservation actions produced these recoveries. In total, 360 species that qualified as AZE species in 2005 no longer qualified by 2018 (45% of those listed in 2005) due to improved knowledge of distribution or taxonomy (83%), genuine improvements resulting in species being downlisted to lower categories of extinction risk (12%), genuine range expansion of species such that they are no longer restricted to single sites (4%), or deterioration to extinction (1%). Our results show that while protected areas and site management are important to the successful conservation of AZE species, other conservation actions, such as species‐level management or improved laws and policies, are also essential to safeguard these species from extinction. Sixty‐eight percent of the original 2005 AZE sites are now fully or partially covered by protected areas, an increase of almost 20% in 15 years. Yet today, only 64% of current (2018) AZE sites are fully or partially covered by protected areas, with 36% lacking any formal protection. Continued efforts to safeguard and manage AZE sites would benefit not only the 1, 483 AZE species but also potentially another 1, 359 Critically Endangered and Endangered amphibian, bird, and mammal species whose distributions overlap with AZE sites. Abstract : By 2018 Alliance for Zero Extinction 360 species that qualified as AZE species in 2005 no longer qualified (45% of those listed in 2005) due to improved knowledge of distribution or taxonomy (81%), genuine improvements resulting lower categories of extinction risk (12%), genuine range expansion of species (6%), or deterioration to extinction (1%). While protected areas and site management are important to the successful conservation of AZE species, other conservation actions, such as species‐level management or improved laws and policies, are also essential to safeguard these species from extinction. Sixty‐eight percent of the original 2005 AZE sites are now fully or partially covered by protected areas, an increase of almost 20% in 15 years. Yet today, only 64% of current (2018) AZE sites are fully or partially covered by protected areas, with 36% lacking any formal protection.